Regulation of Tyrosinase Gene Expression by Retinoic Acid Pathway in the Pacific Oyster Crassostrea gigas - Qianqian Jin; Chuncao Huo; Wenhao Yang; Kaidi Jin; Shuai Cai; Yanxin Zheng; Baoyu Huang; Lei Wei; Meiwei Zhang; Yijing Han; Xuekai Zhang; Yaqiong Liu; et al. (International Journal of Molecular Sciences, 2022)
Retinoic acid (RA) plays important roles in various biological processes in animals. RA signaling is mediated by two types of nuclear receptors, namely retinoic acid receptor (RAR) and retinoid x receptor (RXR), which regulate gene expression by binding to retinoic acid response elements (RAREs) in the promoters of target genes. Here, we explored the effect of all-trans retinoic acid (ATRA) on the Pacific oyster Crassostera gigas at the transcriptome level. A total of 586 differentially expressed genes (DEGs) were identified in C. gigas upon ATRA treatment, with 309 upregulated and 277 downregulated genes. Bioinformatic analysis revealed that ATRA affects the development, metabolism, reproduction, and immunity of C. gigas. Four tyrosinase genes, including Tyr-6 (LOC105331209), Tyr-9 (LOC105346503), Tyr-20 (LOC105330910), and Tyr-12 (LOC105320007), were upregulated by ATRA according to the transcriptome data and these results were verified by real-time quantitative polymerase chain reaction (RT-qPCR) analysis. In addition, increased expression of Tyr (a melanin-related TYR gene in C. gigas) and Tyr-2 were detected after ATRA treatment. The yeast one-hybrid assay revealed the DNA-binding activity of the RA receptors CgRAR and CgRXR, and the interaction of CgRAR with RARE present in the Tyr-2 promoter. These results provide evidence for the further studies on the role of ATRA and the mechanism of RA receptors in mollusks.